Analisis Rendahnya Percaya Diri dan Motivasi Siswa dalam Pembelajaran Senam Lantai di Kelas VII-7 SMP Negeri 1 Masbagik - M. Ardillah; Rina Nopiana (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Floor gymnastics is a topic within the Physical Education, Sports, and Health (PJOK) curriculum that requires students to possess courage, motor coordination, and self-confidence. However, many students still exhibit low self-confidence and learning motivation, limiting their participation in practical activities. This situation is influenced by a fear of injury, embarrassment about making mistakes in front of classmates, a lack of interest in the subject matter, and a lack of variety in teaching methods. This study aims to analyze the factors contributing to students' low self-confidence and learning motivation and to identify the efforts made by the teacher to improve these aspects during floor gymnastics lessons for Class VII-7 students at SMP Negeri 1 Masbagik. The study employs a qualitative approach with a descriptive method. Participants included a PJOK teacher and Class VII-7 students selected via purposive sampling. Data were collected through observation, interviews, and documentation, and validated using source and technique triangulation. The results indicate that low student self-confidence stems primarily from the fear of injury, embarrassment, and the fear of being mocked by peers. Meanwhile, low learning motivation is influenced by a lack of student interest in floor gymnastics and the use of limited teaching methods. To address these issues, the teacher collaborated with Teacher Professional Education (PPG) students to implement several strategies, including creating a safe learning environment, providing positive reinforcement, employing engaging teaching methods, and conducting exercises in a gradual manner. These efforts successfully enhanced the students' courage, self-confidence, learning motivation, and active participation in floor gymnastics lessons.